An artifact of the rotation of too few factors: Study orientation VS. train anxiety - Mote, Jr., Thomas A. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
A series of factor analyses was performed upon data obtained from 170 university students. It was found that the commonly accepted factor analysis “stop” criterion calling for cessation of factor extraction with the last factor attaining an eigenvalue of one resulted in an unrealistic factor structure. It was demonstrated that the extraction and rotation o f two additional factors produced a more meaningful pattern of factors. It was suggested that the conservative investigator might make use of only those factors attaining eigenvalues equal to or greater than one, but that the initial extraction and rotation of a few additional factors may lead to an improved understanding of the relationships underlying the data.